Analisis Pemberian Kredit Terhadap Rentabilitas Pada Sektor Keuangan Sub Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2014-2018 - Tri Amalia Sukarno (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2021)
This study aims to examine and provide empirical evidence regarding the analysis of credit granting towards profitability in the Banking Sub-Sector Companies. The independent variable used in this study is the provision of credit and the dependent variable used in this study is profitability. The hypothesis proposed is